Photosynthetic Bacteria (PSB) as A Mechanism for Water Quality Improvement - Azhari, Nurazira; Abustan, Muhammad Salleh (Recent Trends in Civil Engineering and Built Environment, 2024)
Water is an important substance on earth where all living things are depending on it to survive. However, water pollution, coupled with the restricted supply of clean water, has long been one of the most talked-about or debated topics that place a significant burden on the environment. The deteriorating water quality consequently caused damage to the environment and human health which include the destruction of biodiversity and aquatic ecosystem, food chain disruption and human diseases. To address this challenge, an ecologically friendly and cost-effective treatment technology is required in tandem with a shift toward sustainable development. Hence, this paper is intended to understand the characterization of Photosynthetic Bacteria (PSB) and the effectiveness of PSB towards water quality improvement. The experimental design will be conducted as a batch process in a controlled environment. Four sets of different batch experiments at different types of sample preparation. The data collected in 12 days that conjunction with the pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Ammonia Nitrogen are utilized after the laboratory experiment. The result of BOD, COD and Ammonia Nitrate before adding PSB is 2.16 mg/L, 23.00 mg/L and 4.31 mg/L respectively. When the presence of PSB showed the result of BOD, COD and Ammonia Nitrogen is 1.91 mg/L, 12.00 mg/L and 3.55mg/L respectively. Thus, this study found that supplementing with PSB might dramatically lower the concentrations of BOD, COD and Ammonia Nitrate.